Edge effects without habitat fragmentation? Small mammals and a railway in the Atlantic Forest of southern Brazil. Issue 3 (11th February 2015) - Cerboncini, Ricardo A. S.; Roper, James J.; Passos, Fernando C.
Abstract: Edge effects have been studied extensively in fragmented landscapes, often with conflicting findings. Edge effects may also be important in other situations, such as linear clearings (e.g. along roads, power lines or train tracks). We tested for responses of small mammals to a narrow (c. 10 m) linear clearing created by a railway in the largest area of Atlantic Forest in southern Brazil. Only two environmental variables, light intensity and train noise, were greatest at the edge and decreased with distance from the edge. Temperature differed (greater extremes and more variable) only at the edge itself. The few small mammal species that were only rarely captured at the edge resulted in an apparent edge-effect with respect to species richness. The abundance of small mammals, however, was independent of distance from the railway. There was no correlation between resource availability at the tracks and abundance of small mammals. Edge effects were minimal, which suggests that narrow railways (in contrast with roads) in unfragmented landscapes probably do not have a significant impact (if any) on wildlife, as found elsewhere and especially in tropical forests. The use of railways instead of roads is a potential strategy to minimize the effects of traversing important habitats for commercial reasons.